MODIFIKASI PEMBUAT MOL LIMBAH ORGANIK BAHAN PRAKTIKUM DI LABORATORIUM POLITEKNIK PERTANIAN NEGERI PAYAKUMBUH - Maiza, Linda Tri; Yubniati, Yubniati; Hermansyah, Rio (Politeknik Pertanian Negeri Payakumbuh, 2021)
Local microorganism made in bio activator of making compost and liquid organic fertilizer that can be used for plant cultivation activaties in intitututional environment. All this time, local microorganism maker tool using plastic bucket with lid, produce local MOL is still low, which is charecterized by a foul-smelling aroma of local microorganism, the resulting solution is coarsely precipitated, also not efficient at harvest time. The purpose of this research is to know the performence of the local microorganism maker tool which has been modified. Observation include in term of scent quality, clean liness of solution time efficiency and energy Testing of unmodified local microorganism maker tool and which have been modified by using vegetables and fruit. From the iest result show that the modified local local microorganism maker tols with filter and faucet produce local microorganism better quality, which are indicated by typical scent of local microorganism and cleanliness of solution, its doest’nt cause a problem of time and energy at harvest time, it can be concluded that a modified local microorganism maker tool with filter and faucet at the bottom of the container give better quality of local microorganism.